The capabilities approach and values of sustainability: Towards an inclusive Pedagogy - Roberto Sanz Ponce; José A. Peris Cancio; Juan Escámez Sánchez (Journal of Innovation & Knowledge (JIK), 2018)
Different models of development have a different impact on sustainability. In this paper, we contrast the development model as growth of the Gross Domestic Product (GDP), dominant in economic theories, with the model of human development or capabilities. The objective is to show the development of capabilities as a theoretical-practical perspective to guide education towards sustainability, a goal assigned by UNESCO. The method used is hermeneutic. The conclusions are: the capabilities approach defends the values required for sustainability and this approach convincingly argues for the political principles and good practices that should govern education.
Keywords: I24; I25; 650; Economic models; Development; Capabilities approach; Sustainability; Values of sustainability